Slc26a3 deficiency is associated with epididymis dysplasia and impaired sperm fertilization potential in the mouse. Issue 8 (7th September 2018) - El Khouri, Elma; Whitfield, Marjorie; Stouvenel, Laurence; Kini, Archana; Riederer, Brigitte; Lores, Patrick; Roemermann, Dorothee; di Stefano, Gabriella; Drevet, Joël R.; Saez, Fabrice; Seidler, Ursula; Touré, Aminata
Abstract : Members of the solute carrier 26 (SLC26) family have emerged as important players in mediating anions fluxes across the plasma membrane of epithelial cells, in cooperation with the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel. Among them, SLC26A3 acts as a chloride/bicarbonate exchanger, highly expressed in the gastrointestinal, pancreatic and renal tissues. In humans, mutations in the SLC26A3 gene were shown to induce congenital chloride‐losing diarrhea (CLD), a rare autosomal recessive disorder characterized by life‐long secretory diarrhea. In view of some reports indicating subfertility in some male CLD patients together with SLC26‐A3 and ‐A6 expression in the male genital tract and sperm cells, we analyzed the male reproductive parameters and functions of SLC26A3 deficient mice, which were previously reported to display CLD gastro‐intestinal features. We show that in contrast to Slc26a6, deletion of Slc26a3 is associated with severe lesions and abnormal cytoarchitecture of the epididymis, together with sperm quantitative, morphological and functional defects, which altogether compromised male fertility. Overall, our work provides new insight into the pathophysiological mechanisms that may alter the reproductive functions and lead to male subfertility in CLD patients, with a phenotype reminiscent of that induced by CFTR deficiency in the male genital tract. Abstract : SLC26A3 acts as a chloride/bicarbonate exchanger, highly expressed in the gastrointestinal, pancreatic and renal tissues. In humans, mutations in the SLC26A3 gene were shown to induce congenital chloride‐losing diarrhea (CLD), a rare autosomal recessive disorder characterized by life‐long secretory diarrhea. In view of some reports indicating subfertility in some male CLD patients together with SLC26‐A3 expression in the male genital tract and sperm cells, we analyzed the male reproductive parameters and functions of SLC26A3 deficient mice. We show that in addition to CLD gastro‐intestinal features, deletion of Slc26a3 is associated with severe lesions and abnormal cytoarchitecture of the epididymis, together with sperm quantitative, morphological and functional defects, which altogether compromised male fertility.